The impact of sleep quality and disorders on the risk of obesity – physiological mechanisms and health implications - Jaskółka, Magdalena; Cogiel, Kinga; Trytek-Miś, Karolina; Ochman-Pasierbek , Patrycja (Journal of Education, Health and Sport, 2025)
Introduction and Purpose: Sleep is a biological process essential for immune function, brain development, memory consolidation and emotional regulation. Sleep restriction affects metabolic processes, hormone regulation and coagulation processes and is implicated in various diseases, including for example type 2 diabetes, hypertension, stroke and heart disease. The purpose of our study is to examine the impact of sleep quality on obesity and related diseases. We aim to understand how improving sleep habits can reduce the risk of obesity and its related health issues. Brief Description of the State of Knowledge: Sleep deprivation disrupts hormonal regulation, reducing leptin and increasing ghrelin, leading to overeating and weight gain. Circadian rhythm disturbances also promote insulin resistance and fat storage. Obesity further impairs sleep quality, increasing the risk of metabolic disorders, including type 2 diabetes and hypertension. In pediatric populations, inadequate sleep is associated with higher BMI and an elevated risk of obesity. Summary: Insufficient sleep alters hormonal regulation, promoting overeating and increasing obesity risk, which exacerbates metabolic dysfunction. Addressing sleep disorders and promoting healthy sleep and diet are essential for prevention.